Serum adenosine deaminase activity: A novel test for early diagnosis of pulmonary tuberculosis - What about efficacy? (Journal of Fatima Jinnah Medical University, 2022)
Background: Pulmonary tuberculosis is a tremendous public health problem, increasing significantly, especially in developing countries. Getting a TB-free globe appears to be not more than a dream. Mycobacterial culturing is the gold standard for precise diagnosis but requires six-week time, in the meantime, patients remain a source of inadvertent disease dissemination in the community. The unavailability of sputum also poses a challenge several times. As adenosine deaminase level measurement is easy, rapid and independent of a sputum sample, this study was conducted to determine the diagnostic efficacy of adenosine deaminase activity for pulmonary tuberculosis.Patients and methods: This prospective study was conducted at Pulmonology-OPD, Gulab Devi Chest Hospital, Lahore, from 01-01-2019 to 30-06-2019. A total of 300 sputum smear-positive patients with clinical and radiological evidence consistent with diagnosis of pulmonary tuberculosis and 30 normal participants without any clinical, radiological or haematological evidence of tuberculosis were included. While, smear-negative patients and those having any evidence of hepatic disease, hematopoietic malignancy, infectious mononucleosis, typhoid or pregnancy were excluded. The serum ADA level of each participant was determined. All patients were subjected to AFB culture. Diagnostic accuracy was determined by considering sputum culture as a gold standard.Results: At cut-off value of >15 IU/L, a sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of 98.30%, 100.00%, 100.00%, 85.71%, 98.46% respectively were defined.  Conclusion: Serum ADA level, having excellent sensitivity and specificity, can diagnose pulmonary tuberculosis even if sputum sample is not available.
Keywords: Serum; ADA level; TB-diagnosis; Sensitivity; Specificity